Disappearance at Devil's Rock : a novel - Tremblay, Paul (William Morrow, 2016)
When her fourteen-year-old son disappears during a summer sleepover at Devil's Rock, Elizabeth and other residents of the town begin to see his ghost throughout the town, which leads her to believe that he is dead. She tries to maintain a sense of calm to help her younger daughter, Katie, but her anxiety builds when she begins to find crumpled pages of Tommy's journal which contain disturbing connections between Tommy's father's death, a stranger named Arnold, and a macabre folk tale.